Proceedings of the Thirty-Eighth Annual ACM Symposium on Theory of Computing 2006
DOI: 10.1145/1132516.1132553
|View full text |Cite
|
Sign up to set email alerts
|

The PCP theorem by gap amplification

Abstract: We present a new proof of the PCP theorem that is based on a combinatorial amplification lemma. The unsat value of a set of constraints C = {c1, . . . , cn}, denoted UNSAT(C), is the smallest fraction of unsatisfied constraints, ranging over all possible assignments for the underlying variables.We describe a new combinatorial amplification transformation that doubles the unsat-value of a constraint-system, with only a linear blowup in the size of the system. The amplification step causes an increase in alphabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
378
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(384 citation statements)
references
References 23 publications
6
378
0
Order By: Relevance
“…(7) or Eq. (6), that the trace tr(U (s 1 )U (s 2 )...U (s m )) can be reduced to a trivial trace of the identity matrix by canceling successive appearances of U (s)U (s + D/2) and replacing them with 1 1. The contribution of such choices to E 1 is proportional to a return probability of a random walk on a Cayley tree as will be seen.…”
Section: Lower Bounds and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) or Eq. (6), that the trace tr(U (s 1 )U (s 2 )...U (s m )) can be reduced to a trivial trace of the identity matrix by canceling successive appearances of U (s)U (s + D/2) and replacing them with 1 1. The contribution of such choices to E 1 is proportional to a return probability of a random walk on a Cayley tree as will be seen.…”
Section: Lower Bounds and Numerical Resultsmentioning
confidence: 99%
“…Since expander graphs have a large number of applications in problems dealing with classical statistics, such as in error-correcting codes [5], derandomization, and the PCP theorem [6], to name a few, it seems worth further exploring the quantum case.…”
mentioning
confidence: 99%
“…Thus, even in light of recent advances in the computational efficiency of PCPs [BS08,Din07,MR08,BCGT13b], it seems wise to first investigate efficient implementations of SNARGs in the preprocessing model, which is a less demanding model because it allows G to conduct a one-time expensive computation "as a setup phase". Despite the expensive preprocessing, this model is potentially useful for many applications: while the generator G does require a lot of work to set up the system's public parameters (which only depend on the given circuit C but not the input to C), this work can be subsequently amortized over many succinct proof verifications (where each proof is with respect to a new, adaptively-chosen, input to C).…”
Section: Motivationmentioning
confidence: 99%
“…Locally testable codes have implicitly been a subject of active study ever since the work of Blum, Luby, and Rubinfeld [1990] that showed that (effectively) the Hadamard code is 3-locally testable. They play a major role in the construction of PCPs Safra, 1998, Arora et al, 1998] from the early days of this theorem and continuing through the recent work of Dinur [2007]. Their systematic investigation was started in [Goldreich and Sudan, 2006] and yet most basic questions about their limits remain unanswered (e.g., is there an asymptotically good family of locally testable codes?…”
Section: Locally Correctable and Locally Testable Codes Affine-invarmentioning
confidence: 99%